Role of partogram in the management of spontaneous labour in primigravida and multigravida - Penumadu, Kavya Mahesh; Hariharan, C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of this study was to analyze the patterns of labour amongst spontaneous parturients using a WHO modified partogram and compare outcomes of labour and their neonatal outcomes amongst the different partogram patterns Methods: This prospective study was carried out in the labour room of the department of obstetrics and gynaecology of Acharya Vinoba Bhave rural hospital, Sawangi Meghe, Wardha, Maharashtra, over a period of two years i.e. from October 2012 to September 2014. Analysis of the progress of labour was done in two hundred and fifty women with the help of modified WHO partogram. The patients were divided into three groups. Group A whose partogram remained to the left of the alert line, group B whose partogram remained between the alert and action line and group C had their partogram crossing the action line. The different types of abnormal labour were studied. The maternal and fetal outcomes were assessed. Results: 67.2% of the women belonged to group A, 22.8% to group B and 10% to group C. Surgical interference and requirement of augmentation increased as the labour curve moved to the right of the alert line. All patients delivered within 12 hours. Timely intervention reduced the incidence of prolonged labour and its sequelae. 82 patients showed abnormal labour patterns. There were no maternal death or neonatal death. Conclusions: The use of modified WHO partogram significantly improves both maternal & neonatal outcome. Routine use of partogram should be implemented in all institutions and all labour rooms in India where delivery care is being given and especially in areas where operative and new-born facilities are lacking to facilitate early referral.